Optimization of ultrasound-microwave synergistic extraction of prebiotic oligosaccharides from sweet potatoes (Ipomoea batatas L.). (June 2019) - Guo, Zebin; Zhao, Beibei; Li, Huang; Miao, Song; Zheng, Baodong
Abstract: In this study, efficient ultrasound–microwave-assisted extraction (UMAE) of prebiotic oligosaccharides from sweet potatoes ( Ipomoea batatas L.) was investigated. Response surface methodology was used to optimize the extraction conditions: extraction time, ultrasonic power, and microwave power. The prebiotic effect of extracted oligosaccharides on Bifidobacterium adolescentis was also investigated. The results show that the processing conditions of UMAE for optimum the yields of prebiotic oligosaccharides from sweet potatoes (PPOS4 and PPOS5) and corresponding absorbance (OD) are 100 s extraction time, 300 W ultrasonic power, and 200 W microwave power. Under these conditions, the experimental yields of PPOS4 and PPOS5 and the corresponding OD were 1.472%, 5.476%, and 2.966, respectively, which match the predicted values well. Compared with the conventional hot-water extraction (HWE), microwave-assisted extraction (MAE), and ultrasound assisted extraction (UAE) methods, the UMAE procedure exhibited significantly high extraction efficiency ( p  < 0.05). Comparison of SEM images of tissues of the sweet potatoes after extractions indicate microfractures and disruption of cell walls in the potato tissues. These results confirm that UMAE has great potential and efficiency in the extraction of bioactive substances in the food and medicinal industries. Industrial relevance: Ultrasound–microwave-assisted extraction is a new process technology that combines the ultrasonic and microwave methods. It makes full use of the high-energy effect of microwaves and ultrasonic cavitation. And it overcomes the shortcomings of conventional, ultrasonic, and microwave extractions. Fast, efficient extraction using this method can be realized at low temperature under ambient conditions, enhancing competition of industries to be more ecologic, economic and innovative. Highlights: Compared with the conventional HWE, MAE, and UAE methods, UMAE exhibited significantly high extraction efficiency. The optimum conditions of UMAE for prebiotic oligosaccharides are 300 W ultrasonic and 200 W microwave power for 100 s. Cell walls of purple sweet potato tissues showed microfractures and disruption under SEM after UMAE procedure.